(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
This article aims to perform an evaluation on the public policy of workers’ health through a case study of the municipality of Rio de Janeiro. It seeks to understand the relationship of injuries and deaths resulting from work accidents with the increase/decrease of government measures on prevention and care for primary care of workers. From the data provided by the State and Municipal Secretariats of Rio de Janeiro, in the budget laws, specialized bibliography and in the analysis of results obtained at IBGE and the Labor Observatory, it is feasible to understand the impact that this issue causes not only on the individual but also on the entire community. The present study will also present how public managers organized themselves with the spread of the Covid-19 pandemic and the framing of this virus as a resulting hypothesis of work accidents.